Remote execution of physical tasks by putting into contributionDOSN: Case of Money Transfer (International Journal of Scientific Research and Management (IJSRM), 2023)
Distributed Online Social Networks (DOSN) provide some advantages that are not yet fully exploited. It can help reduce cost especially when it comes to manage remote physical agents to fulfill some tasks under delegation of other agents that are weakly coupled. This paper tackles the problem of structuring and organizing such a network and a case study is applied on international money transfer. Recent studies showed that the difference between the amounts of money transfer between less developed and developed countries is not too high. The finance institutions for money transfer are widespread but at international level, only few companies share the market giving the lion share to Western Union and Moneygram. Building a social network of “gentlemen” can transform two international transfers to two or more national transfers. It can then reduce the charges of international transfers, speed up at time the process of money transfer, include more people that are outside the banking system. A prototype is constructed using three key concepts to solve arisen problems. Firstly, the gentlemen approach uses some kind of godfather relationship used in most djangui unions in Cameroon to welcome new members. The graph database Neo4J was chosen to ease the process of identifying the chain of godfathers in case a “bad guy” joins and abuse members of the network. Secondly, the knapsack problem in all is varieties is implemented in case the amount to be transferred from one country to another could not match a one-to-one relationship. Thirdly, a signcryption mechanism is used to solve the cryptographic functionalities that occur during message exchanges on the platform. Due to the fact that such social network has to dealt with trust, reputation, privacy and security, it can be considered as a powerful tool for investigating societal problems such as financing terrorism or deception on the Internet. A game theory can then be applied to detect the conditions making the network not interesting to hackers.